Tata Kelola Digital Layanan Lalu Lintas Jalan Tol di Indonesia: Studi Aplikasi Travoy Jasa Marga - Setiawan, Mohamad Agus; Hartoyo; Seminar, Kudang Boro; Sartono, Bagus; Fitriati, Rachma (Research and Development Agency Ministry of Home Affairs, 2024)
Digital transformation has transformed the governance approach into digital governance, essential in improving performance and service quality in various sectors, including the toll road industry. This article explores the implementation of digital governance in toll road traffic services in Indonesia. The research method uses a qualitative approach with data collection techniques through observation, literature studies, focus group discussions, and in-depth interviews with a study time of six (6) months from September 2023 to February 2024. The study results show that toll road users face various problems in toll road traffic services in Indonesia, such as severe traffic congestion, over-capacity rest areas, dirty toilets, lack of gas station facilities, and lack of information about congestion points and alternative routes. As an Indonesian state-owned enterprise engaged in toll road operations, PT. Jasa Marga Tbk. launched the Travoy application to provide practical solutions for toll road users to get the necessary information services, facilitate the search for rest areas, and reduce congestion by managing traffic distribution. The study results confirm the importance of continued investment in digital technology and effective data processing to ensure the satisfaction and convenience of future toll road users.